2020
DOI: 10.14202/vetworld.2020.354-359
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical study to detect glucagon and insulin hormones in pancreas of camel and buffalo

Abstract: Background and Aim: Glucagon plays a significant role in glucose homeostasis by controlling hepatic glucose output in terms of both hypoglycemic and normoglycemic conditions. This study aimed to determine the amount and intensity of insulin and glucagon in addition to estimating the relationship between α- and β-cells for two animals, camel and buffalo. Materials and Methods: Twenty fresh pancreas samples were collected from 10 buffalo and 10 camel adults immediately after slaughter from AL-Kut abatto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 14 publications
8
4
0
Order By: Relevance
“…The present study revealed variation in the size of pancreatic islets during postnatal development of the pancreas in camels where the pancreatic islets increased in diameter with age, from 70.3 ± 1.5 µm in 4 years to 97 ± 1.6 µm in 18 years in the camel pancreas (Table . 3), which is in agreement with the results of Bargooth et al (2020), who found that the diameter of a pancreatic islet in an adult camel was 98 ± 0.5 µm. The increase in pancreatic islet size with age may be related to the various needs of hormone secretion by the pancreatic islets for metabolism in the camel pancreas, which is primarily influenced by blood glucose levels.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study revealed variation in the size of pancreatic islets during postnatal development of the pancreas in camels where the pancreatic islets increased in diameter with age, from 70.3 ± 1.5 µm in 4 years to 97 ± 1.6 µm in 18 years in the camel pancreas (Table . 3), which is in agreement with the results of Bargooth et al (2020), who found that the diameter of a pancreatic islet in an adult camel was 98 ± 0.5 µm. The increase in pancreatic islet size with age may be related to the various needs of hormone secretion by the pancreatic islets for metabolism in the camel pancreas, which is primarily influenced by blood glucose levels.…”
Section: Discussionsupporting
confidence: 92%
“…The pancreatic islets in the present study were scattered throughout the camel pancreas and had varied shapes, which is consistent with previous research (Bargooth et al, 2020). In contrast to the findings of the current study in camels, Hafez et al (2015) noticed clear and strong delineation in horses.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations